Challenges and Strategies of Chemical Analysis of Drugs of Abuse and Explosives by Mass Spectrometry - Habib, Ahsan; Bi, Lei; Hong, Huanhuan; Wen, Luhong (Frontiers in Chemistry, 2021)
In analytical science, mass spectrometry (MS) is known as a ‘gold analytical tool’ because of its unique character of providing the direct molecular structural information of the relevant analyte molecules. Therefore, MS technique has widely been used in all branches of chemistry along with in proteomics, metabolomics, genomics, lipidomics, environmental monitoring etc. Mass spectrometry-based methods are very much needed for fast and reliable detection and quantification of drugs of abuse and explosives in order to provide fingerprint information for criminal investigation as well as for public security and safety at public places, respectively. Most of the compounds exist as their neutral form in nature except proteins, peptides, nucleic acids that are in ionic forms intrinsically. In MS, ion source is the heart of the MS that is used for ionizing the electrically neutral molecules. Performance of MS in terms of sensitivity and selectivity depends mainly on the efficiency of the ionization source. Accordingly, much attention has been paid to develop efficient ion sources for a wide range of compounds. Unfortunately, none of the commercial ion sources can be used for ionization of different types of compounds. Moreover, in MS, analyte molecules must be released into the gaseous phase and then ionize by using a suitable ion source for detection/quantification. Under these circumstances, fabrication of new ambient ion source and ultrasonic cutter blade-based non-thermal and thermal desorption methods have been taken into account. In this paper, challenges and strategies of mass spectrometry analysis of the drugs of abuse and explosives through fabrication of ambient ionization sources and new desorption methods for nonvolatile compounds have been described. We will focus the literature progress mostly in the last decade and present our views for the future study.